Colonisation endpoints in Streptococcus pneumoniae vaccine trials - Auranen, Kari; Rinta-Kokko, Hanna; Goldblatt, David; Nohynek, Hanna; O’Brien, Katherine L.; Satzke, Catherine; Simell, Birgit; Tanskanen, Antti; Käyhty, Helena (Vaccine, 2013)
•We consider evaluation of vaccine efficacy against pneumococcal colonisation.•The need to carefully define the efficacy parameter is emphasised.•Efficacy against acquisition should be preferred over efficacy against prevalence.•We review methods to estimate efficacy against acquisition from cross-sectional data. Evaluating vaccine efficacy for protection against colonisation (VEcol) with bacterial pathogens is an area of growing interest. In this article, we consider estimation of VEcol for colonisation with Streptococcus pneumoniae (the pneumococcus). Colonisation is a common, recurrent and multi-type endpoint that requires both careful definition of the vaccine efficacy parameter and the corresponding method of estimation. We review recent developments in the area and provide practical guidelines for choosing the estimand and the estimation method in trials with a colonisation endpoint. We concentrate on methods that are based on a cross-sectional study design, in which only one nasopharyngeal sample is obtained per study subject.